Relationship Between Instagram's Social Media Use Intensity And Self-Acceptance in Students - Cholili, Abd. Hamid; Pratiwi, Maya Sistania (Kariman: Jurnal Pendidikan Keislaman, 2023)
Some people have the main goal in using social media, namely to get satisfaction when their psychological needs are met, that way someone will be motivated to continue meditating. social media so that when he gets satisfaction through the many positive comments and is liked by many people, this encourages someone to continue sharing photos or videos of his activities via Instagram. But if he is dissatisfied with what he has uploaded on Instagram so that he feels neglected and unappreciated, it will cause someone to be reluctant to upload his photos again. The number of negative comments that often appear on Instagram can trigger someone to do unwanted things, one of which is Self Low acceptance. Self-acceptance a low is characterized by someone who feels worthless, depressed, difficult to adapt to their environment, and lacks motivation because they often blame and hate themselves. Instagram social media use and self-acceptance on students. This research uses quantitative research methods. The subjects in this study were 48 students. Data analysis in this study used product analysis moment. product analysis moment aims to test whether there is a relationship (correlation) between variables. Collecting data using the method of distributing scale questionnaires. The results of this study using the product test moment which shows the results of the analysis of data correlations sig value (2-tailed = 0.000) <0.05 then Ho is rejected, meaning that Ha is accepted so that the conclusion is obtained There is a relationship between Intensity of Use of Instagram Social Media and Self-acceptance. While the Pearson value correlation obtained by 0.622 means that the Intensity of Use of Social Media Instagram contributes 62.2% to Self Acceptance, the remaining 37.8% is influenced by other factors.